The role of the dancer - Inga María Olsen 2000- (2022)
Dancers are often required to change roles quite rapidly throughout their workday, it can be a bit like being the dentist for a second and the other you are the patient. It is the dancer who is obedient to the choreographer's work and set material and it is the dancer as a maker who is also producing the content with the choreographer. Both of these “hats” connect to the role of being a dancer in a company, which has always been my primary goal. The role of the dancer has taken more steps towards the role of the independent dancer, and away from the traditional role. In this writing I will analyze the role of a company dancer within a creative process, based on my experience of being a part of two processes from the dancers' graduation pieces in Iceland Academy of the Arts. Run/Through by Katrín Gunnarsdóttir and Phygital Glitch by Gígja Jónsdóttir. With this examination I will have for reference Twyl Tharp's book “The Creative Habit, learn it and use it for life” and Pamela Newell writings about dancers' roles within creative processes. I also had an interview with Aðalheiður Halldórsdóttir to get an even better insight into the dancer's work environment. Aðalheiður is a dancer and a choreographer who has worked for many years in the Icelandic Dance Company and as an independent artist, both as a dancer and choreographer. Within this profession where the creative processes can become highly fluid and the division of roles sometimes unclear it can be a challenge to place yourself as a dancer in the creative process. By analyzing these different ways of working in relation to those two creative processes, I hope to offer clarity of the dancer's roles and what affect the dancer has for my future as a dancer.